Formulasi Biskuit sebagai Makanan Tambahan Balita Gizi Kurang menggunakan Tepung Tempe - Winarti, Pramita Ayu; Kristianto, Yohanes; Setyobudi, Sugeng Iwan; Palupi, Fitria Dhenok (Media Gizi Kesmas, 2024)
Administration of food supplement to under nutrition children is important as an effort to overcome the problem. Tempe is a potential local food since it contains abundant of protein, dissolved nitrogen, free fatty acids, and have high digestibility. The purpose of this study was to produce biscuit using tempeh as food supplement. The experiments were carried out using a completely randomized design (CRD). Biscuit formulation was carried out by changing the proportion of wheat flour: tempeh flour (b/b) with levels of P0 = 100:0, P1 = 70:30, P2 = 60:40, and P3 = 50:50 respectivley. Protein, fat, ash and water content of biscuits were determined respectively by kjeldahl, soxhlet and gravimetric methods. The nutritional content of biscuits was compared with SNI and food supplement standards. The colour of the biscuits were analyzed using the colour difference ratio (CDR) method. Biscuit qualities were also assessed based on sensory tests. The results showed that tempeh flour significantly increased protein and ash content. The use of tempeh flour has no significant effect on the energy content, levels of carbohydrates, fat, water, and colour of the biscuits. The formula of P3 meets SNI the requirements for biscuits and food supplement standard requirements with an energy content of 473 Kcal, 16.8 gr protein, 20.3 gr fat, 55.8 gr carbohydrates, 1.3 gr ash, and 5.8 gr water for 100 grams of the product. The use of tempeh flour in the biscuit formulation increased the PST and PER scores, and only slightly decreased the SAA, NPU and digestibility scores. Tempeh biscuits from the best treatment can be used as PMT for handling malnutrition with a serving size of 30-40 grams and given once per day.